Constructing Teacher Identity: Pre-Service Teacher Resilience in School-based Practicum Experiences - Concilianus Laos Mbato; Yoannes Yuka Krisdianata (Journal of English Language Teaching and Linguistics, 2022)
Constructing teacher identity is important for pre-service teachers, especially when taking part in teacher training practicums in school. Nonetheless, they faced many adversities, such as passive students, negative emotions, and anxiety. Therefore, pre-service teachers need to be aware of their capacity for resilience. This study aimed to discover the resilience factors pre-service teachers had in coping with the problems found in teacher training practicums in schools in constructing their teacher identity. A mixed-method study from questionnaires and semi-structured interviews was employed to gather quantitative and qualitative data. The participants reported that they faced hard times but displayed high resilient ability. It was influenced by their perseverance, ability to reflect,  adaptive help-seeking,  responses to the negative affect, and emotional regulation. The resilient ability supports the teacher identity construction after conducting a teaching practicum in school. Further research needs to consider the number of participants, gender, age, and the school levels where the teaching practicums are conducted to gain more perspectives on pre-service teachers’ resilience.